A direct comparison of monomeric vs. dimeric and non-annulated vs. N-annulated perylene diimide electron acceptors for organic photovoltaics. (13th March 2019) - Nazari, Maryam; Cieplechowicz, Edward; Welsh, Thomas A.; Welch, Gregory C.
Abstract : A systematic structure–property-function evaluation of four structurally related organic photoactive materials based on the perylene diimide chromophore. Abstract : Herein we report on four perylene diimide (PDI) variants to study the effects that N -annulation and dimerization have on optoelectronic properties and organic solar cell device performance. The PDI compounds were synthesized following a scalable and efficient procedure and studied by cyclic voltammetry, solution and solid-state optical absorption spectroscopy, emission spectroscopy, and density functional theory analysis. The thin-film morphology was probed by optical and atomic force microscopy. Dimerization stabilized the frontier molecular orbital energy levels and reduced aggregation in the thin-films. N -Annulation resulted in a destabilization of the frontier molecular orbital energy levels in both the monomers and dimers and enabled the formation of smoother films with smaller domain sizes. Each PDI molecule was evaluated as a non-fullerene acceptor in bulk-heterojunction solar cells using the donor polymers PTB7-Th and PffBT4T-2OD. The dimers outperformed the monomers, while N -annulated PDIs led to devices with higher open-circuit voltages.